Avaliação hidrogeológica do Alto da Bacia do Rio Jiquiriçá - BA - Santos, Cristovaldo dos (2012)
Banca Examinadora: Prof. Dr. Luiz Rogério B. Leal (UFBA); Prof. Dr. Sérgio Augusto de M. Nascimento; Profa. Dra. Iara Brandão de Oliveira (UFBA); Prof. Dr. José Márcio Lins Marinho (UFC)